Dietary energy density affects fat mass in early adolescence and is not modified by FTO variants - Johnson, L; Jaarsveld, V; Emmett, P; Rogers, I; Ness, A; Hattersley, A; Timpson, N; Smith, G; Jebb, S (Public Library of Science, 2009)
BACKGROUND: Dietary energy density (DED) does not have a simple linear relationship to fat mass in children, which suggests that some children are more susceptible than others to the effects of DED. Children with the FTO (rs9939609) variant that increases the risk of obesity may have a higher susceptibility to the effects of DED because their internal appetite control system is compromised. We tested the relationship between DED and fat mass in early adolescence and its interaction with FTO variants. METHODS AND FINDINGS: We carried out a prospective analysis on 2,275 children enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC). Diet was assessed at age 10 y using 3-day diet diaries. DED (kJ/g) was calculated excluding drinks. Children were genotyped for the FTO (rs9939609) variant. Fat mass was estimated at age 13 y using the Lunar Prodigy Dual-energy X-ray Absorptiometry scanner. There was no evidence of interaction between DED at age 10 y and the high risk A allele of the FTO gene in relation to fat mass at age 13 y (beta = 0.005, p = 0.51), suggesting that the FTO gene has no effect on the relation between DED at 10 y and fat mass at 13 y. When DED at 10 y and the A allele of FTO were in the same model they were independently related to fat mass at 13 y. Each A allele of FTO was associated with 0.35+/-0.13 kg more fat mass at 13 y and each 1 kJ/g DED at 10 y was associated with 0.16+/-0.06 kg more fat mass at age 13 y, after controlling for misreporting of energy intake, gender, puberty, overweight status at 10 y, maternal education, TV watching, and physical activity. CONCLUSIONS: This study reveals the multi-factorial origin of obesity and indicates that although FTO may put some children at greater risk of obesity, encouraging a low dietary energy density may be an effective strategy to help all children avoid excessive fat gain.